IMPLEMENTATION OF THE CAMPUS TEACHING PROGRAM IN IMPROVING LITERACY AND NUMERACY COMPETENCE - Harso, Aloisius; Muku, Maria Januari Azi; Wagho, Marianus Salvtore (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2025)
SD Inpres Ende 13 is an elementary school located in the Ende district that is the target of the implementation of the 2024 batch 8 teaching campus program, which is included in the low level of the minimum competency assessment (AKM) results. This assessment will look at and measure the indicator aspects of students' numeracy and literacy abilities. Reading becomes the ability that is assessed from the literacy aspect. Meanwhile, the ability to analyse numbers is the focus of the assessment of numeracy abilities. This community service applies a qualitative method where campus teaching participants, students and teachers will carry out a planned work program to see comprehensive interactions. The increase in students' knowledge and literacy and numeracy skills can be seen from the measurement results due to this community service, where there was an increase from 65% to 88% reaching the good category in literacy, while the results of the numeracy AKM post-test showed a significant increase, namely from 31% to 72%. Positive results were obtained from the qualitative approach process of this service. The implementation of writing competitions, poetry reading, fast and correct counting competitions, creating reading communities and educational games has a positive impact on student learning outcomes.